The Influence of Social-Emotional Development on School Readiness in Early Childhood: A Study of 5–6 Year-Olds in Bogor Regency - Handayani, Oktarina Dwi; Kaffa, Silmi (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Many young children enter formal schooling without adequate social-emotional skills, which hampers their ability to adapt, engage, and succeed in early academic environments. This study aimed to examine the influence of social-emotional development on school readiness among children aged 5–6 years attending preschool in Bogor Regency, Indonesia. The research employed a quantitative correlational design, using purposive sampling to select 152 children enrolled in seven early childhood education institutions. Two validated instruments were used to assess social-emotional development and school readiness. Data were analyzed using Spearman’s rank correlation in SPSS to determine the strength and direction of the relationship between the two variables. The results revealed a strong and statistically significant positive correlation (rs = 0.670, p < 0.01), indicating that children with higher levels of social-emotional competence—particularly in areas such as emotional regulation, independence, cooperation, and empathy—demonstrated greater readiness for school. These children were more capable of adapting to classroom routines, participating in group learning, and performing academically. The study provides empirical evidence supporting the inclusion of structured social-emotional learning (SEL) components in early childhood education programs. It highlights the importance of early intervention strategies to foster emotional and behavioral development as a foundation for formal schooling. However, the study is limited by its restricted geographic scope and relatively small, homogeneous sample, which may limit the generalizability of the findings. Future studies should expand to multiple regions and include more diverse populations to validate and enrich the current results. Longitudinal research is also recommended to explore the sustained impact of early social-emotional development on long-term academic and social outcomes. The findings emphasize the need for integrated efforts among educators, parents, and communities to strengthen children’s readiness for school.